Experimental Research on the Impact of Temperature on the Adhesion Characteristics of Soil-Structure Interface - Tao Qiu; Cheng Liu; Xiaochun Zhong; Yueyue Zhu (Geofluids)
Under the working condition of mud cake, the continuous action between the shield cutter head and the soil on the excavation surface can generate high temperature in the process of shield tunneling and excavation, which changes the characteristic of the adhesion between the soil and the cutter head to intensify the phenomenon of making a mud cake on cutter, finally leading to a vicious circle. To study the effect of temperature on the characteristics of the adhesion of the soil on the surface of the structure, the soil adhesive situation and adhesion force at different interface temperatures were tested through a self-made experiment device. According to the result, it was indicated that the moisture content has a significant effect on the adhesion force of the soil, and the adhesion force firstly increased and then decreased with the increased of the moisture content and reached the maximum value near the plastic limit moisture content. The adhesion force changes very gently when the interface temperature is low. When the temperature reached 50°C, the adhesion force continues to increase as the interface temperature continuously increases except for the soils with high moisture content; moreover, the interface temperature has a great influence on the content of soil adhered on the structure surface. As for the soil with moderate moisture content (ω=21.21~31%), this content of the adhered soil increased exponentially with the increase of interface temperature; this content firstly decreased and then increased when the moisture content was high. When the soil was dry, there was almost no adhered soil on the surface and the interface temperature had no effect on the adhesive situation. By comparing and analyzing the adhesion state of the soil on the surface of the structure, the influence of temperature on the adhesion characteristics is mainly reflected on the variation of the soil moisture content within the influence range of the interface, the variation of the energy required for the destruction of the adhesion interface, and the change of the location of the weakest antistripping plane induced by both before. This research can better understand the law of formation and development of mud cakes and provided a new idea of solving the problem of mud cakes on the cutter head.